The Context (In)Dependence of Low-Fit Brand Extensions - Mathur, Pragya; Malika, Malika; Agrawal, Nidhi; Maheswaran, Durairaj (Journal of Marketing, 2023)
Low-fit brand extensions, while often presenting profitable opportunities for existing brands, are known to meet with varying levels of consumer acceptance. This research identifies conditions in which low-fit extensions can succeed. Specifically, the authors show that the extent to which consumers consider the context in forming judgments (i.e., they are context dependent) determines their acceptance of low-fit extensions. Across four studies, the authors examine the combined effects of context (in)dependence and type of information. Context-dependent consumers form their evaluations on the basis of the type of brand extension information provided, such that providing benefit-based information enhances the evaluations of low-fit extensions, whereas providing attribute-based information leads to a reliance on extension fit and subsequent unfavorable evaluations of low fit extensions. In contrast, context-independent consumers are more likely to base their judgments on extension fit regardless of whether they receive attribute- or benefit-based information. Acceptance of high-fit extensions is unaffected by context (in)dependence and type of information. These findings provide a two-step strategy (i.e., sensitize consumers to context and providing benefit-based extension information) to managers for launching low-fit extensions and leveraging existing parent brand equity.